(untitled) (Research, Society and Development, 2021)
Science has shown the importance of trees in urban environments that, through their ecosystem services, provide quality of life to the population. Thus, taking into account the role of the university as a trainer of human resources and a generator of science applied to the quality of life and the environment, the present study aimed to investigate how the extension event “Arboriza Ponta Grossa”, organized annually by Professors and undergrad students of the State University of Ponta Grossa, responsible for the production and donation of seedlings of tree species and passing on information on the planning of urban afforestation, is inserted in the context of Environmental Education and in the construction of environmental references about the importance of trees in the urban environment. Therefore, the research was based on a qualitative approach and as a data collection tool a questionnaire applied to people who participated in the event was used. The responses to the questionnaires were analyzed based on the frequencies of the responses observed, using tools from the Excel program to build graphs. It was observed that extension events such as “Arboriza Ponta Grossa” can be considered efficient in promoting interaction between the university and the community, in addition to meeting educational and didactic objectives, being an important subsidy for the academic education of future professionals committed to society. The good reach of the public and the population’s adherence to the event demonstrate the high interest of the participants in raising the percentage of plants in urban environments, and reinforce the importance of actions like this to sensitize the community about the ecological, social and economic value of urban forests.